2010
DOI: 10.1111/j.1365-3083.2010.02397.x
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry Study of Blood Cell Subtypes Reflects Autoimmune and Inflammatory Processes in Autoimmune Polyendocrine Syndrome Type I

Abstract: Autoimmune polyendocrine syndrome type I (APS I) is a recessive disorder caused by mutations in the autoimmune regulator (AIRE) gene. AIRE is expressed in medullary epithelial cells where it activates transcription of organ‐specific proteins in thymus, thereby regulating autoimmunity. Patients with APS I have, in addition to autoimmune manifestations in endocrine organs, also often ectodermal dystrophies and chronic mucocutaneous candidiasis. The aim of this study was to characterize immune cell subpopulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 47 publications
6
41
2
Order By: Relevance
“…Recently, we have studied Th17 responses in APECED patients in vivo and found a predominant defect in IL-22 production both in antigenchallenged skin and unexposed skin [18]. Similarly, the composition of the CD4 + population has been reported to be either normal or skewed, and the full pattern of functional Th differentiation has not been studied [17,19,20]. Here, we report the characteristics of the circulating Th cell population in Finnish APECED patients.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Recently, we have studied Th17 responses in APECED patients in vivo and found a predominant defect in IL-22 production both in antigenchallenged skin and unexposed skin [18]. Similarly, the composition of the CD4 + population has been reported to be either normal or skewed, and the full pattern of functional Th differentiation has not been studied [17,19,20]. Here, we report the characteristics of the circulating Th cell population in Finnish APECED patients.…”
Section: Introductionmentioning
confidence: 85%
“…IL-17A production after stimulation was reported either normal or increased, while IL-17F response was reduced [13,15]. One study of five patients reported increased frequency of Th17 cells after stimulation with Candida [16], while another suggested a normal frequency of circulating cells co-expressing CXCR3 and CCR6, surrogate markers for IL-17A-producing cells [17]. Recently, we have studied Th17 responses in APECED patients in vivo and found a predominant defect in IL-22 production both in antigenchallenged skin and unexposed skin [18].…”
Section: Introductionmentioning
confidence: 94%
“…The deficient number, impaired function and diminished FOXP3 expression of T regulatory cells has been reported by several studies [148][149][150][151]. However, whether the defects in APECED regulatory T cells are the result of changes occurring in the thymic environment or in the periphery remains unknown [152].…”
Section: Apeced Pathogenesismentioning
confidence: 96%
“…Regulatory T cells are essential to intestinal tolerance, but in APECED patients they are dysfunctional (8) and express significantly decreased levels of FOXP3 (8,10,11). Only 8 of the 12 patients were available for isolation of live cells and functional suppressive testing.…”
Section: Anti-s Cerevisiae Abs Correlate With the Regulatory T Cell mentioning
confidence: 99%
“…Several studies have reported defects in the number or function of regulatory T cells (Treg) (8)(9)(10)(11), and dendritic cells have been shown to be abnormal (12,13). Practically all patients have neutralizing Abs against type I IFNs (14), which are often the earliest manifestation of the disease, and autoantibodies targeting other cytokines are also found, of which anti-IL-17 and -IL-22 Abs have been linked to impaired defense against Candida (2,15,16).…”
mentioning
confidence: 99%